2018
DOI: 10.1016/j.immuni.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 in Immature Myeloid Precursor Cells Controls Differentiation into Ly6c+CD103+ Monocytic Antigen-Presenting Cells in Tumors

Abstract: CD103 dendritic cells are critical for cross-presentation of tumor antigens. Here we have shown that during immunotherapy, large numbers of cells expressing CD103 arose in murine tumors via direct differentiation of Ly6c monocytic precursors. These Ly6cCD103 cells could derive from bone-marrow monocytic progenitors (cMoPs) or from peripheral cells present within the myeloid-derived suppressor cell (MDSC) population. Differentiation was controlled by inflammation-induced activation of the transcription factor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 46 publications
(75 reference statements)
5
90
0
Order By: Relevance
“…8,36 This is in accordance with our in vitro observations with human monocytes whose differentiation into DCs, maturation, and predominantly the upregulation of CD80 and CD86 was enhanced in the presence of supernatants of irradiated tumor cells. Functionally, this was paralleled by improved stimulation of allogeneic CD8 + , and to a lesser extent also CD4 + T cells with the strongest effects seen with supernatants of 20 Gy-irradiated tumor cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…8,36 This is in accordance with our in vitro observations with human monocytes whose differentiation into DCs, maturation, and predominantly the upregulation of CD80 and CD86 was enhanced in the presence of supernatants of irradiated tumor cells. Functionally, this was paralleled by improved stimulation of allogeneic CD8 + , and to a lesser extent also CD4 + T cells with the strongest effects seen with supernatants of 20 Gy-irradiated tumor cells.…”
Section: Discussionsupporting
confidence: 89%
“…34 Along these lines, it becomes increasingly evident that monocytic cells can give rise to a population of monocytic APCs which are of importance for the stimulation of anti-tumor immune mechanisms during cancer therapy – at least in mouse tumor models. 8,35,36 For anthracycline-based chemotherapy, it has already been shown that dying cancer cells can stimulate the differentiation of recruited monocytes into antigen-presenting DCs. 8 Thus, we hypothesized that similar effects on DC differentiation and maturation may be induced by irradiated, dying cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, IFNγ is known to possess potent antivascular effects (Kammertoens et al, 2017; Qin and Blankenstein, 2000). Moreover, some recent studies have revealed novel mechanisms by which T cell-derived IFNγ remodels the TME to promote antitumor immunity (Ayers et al, 2017; Sharma et al, 2018; Wang et al, 2016). Wang et al (2016) reported IFNγ derived from tumor-infiltrating CD8+ T cells can act upon stromal fibroblasts to reduce GSH in the TME, thereby abrogating tumor resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2016) reported IFNγ derived from tumor-infiltrating CD8+ T cells can act upon stromal fibroblasts to reduce GSH in the TME, thereby abrogating tumor resistance to chemotherapy. Sharma et al (2018) showed that T cell-derived IFNγ acts upon immature myeloid cells to promote their differentiation into CD103+ immunogenic antigen-presenting cells (APCs) through a p53-dependent mechanism. Here we showed that the host response to IFNγ was required for the curative effect of CTX + CD4 AT treatment (Figure S1B), in line with the notion that IFNγ may contribute to tumor rejection by acting on the TME, including disrupting tumor vasculature, reducing stroma-derived GSH, and promoting immunogenic APCs.…”
Section: Discussionmentioning
confidence: 99%